Toxicity of food colours and additives - a review. (2015)
Majority of consumer goods are required to be presented with good aesthetics in order to improve acceptability in terms of colours and in some instances taste. When related to food, beverages and drug products, additives are usually added to mask un-inviting colours, obscure offensive odours and increase taste. Food additives therefore include colourants, sweeteners, preservatives and anti-caking agents. Admissible daily intake limits are often recommended for these additives. Being food products, the amount consumed over time may be subject to individual preferences and thus negating the desire to regulate and control the amount consumed cumulatively. There have been several concerns about the safety of food additives and several batteries of tests, and reports are available in literature. This review attempted to give an update on reports that have surfaced in literature over recent past on the use and safety of food colours and other additives. Some safety concerns have been related to three determinations; cytotoxicity, genotoxicity and induction or potential of inducing mutagenicity. In order to accomplish these targeted evaluations, several tests have been prescribed by International conference on harmonization (ICH), organization for economic co-operation and development (OECD) and European food safety authority (EFSA). It is observed that no single test can give a full proof of safety of these food colours and additives, hence minimal tests are recommended to be carried out in order to guarantee safety of these products. Survey of literature, revealed that once some approved additives or colours become a subject of safety concerns, comprehensive evaluations are carried out by researchers and these have often led to the de-classification of some hitherto reported agents as being non-genotoxic or non-carcinogenic. The declassifications of some food colors and additives as human carcinogens are regularly done following the comprehensive evaluation of results of mutagenicity and genotoxicity tests in vitro and some in vivo tests in mammalian tissues and whole animals. However, such declassifications are often done with caution and the implication is that regular and more comprehensive tests must be carried out. In addition, the requirements of testing for chronic exposures to this and other agents must be emphasized to prevent occurrence of subtle yet terrible side effects resulting from consuming sub-toxic doses of the additives over time.